Pengaruh Kualitas Pelayanan Dan Brad Trust Terhadap Loyalitas Pelanggan Pada Pengguna Jasa Pengiriman PT Pos Indonesia Kantor Cabang Purwakarta - Sriwendiah, Sandra; Sopiah, Siti; Purwadi, Ricky Ekaristy (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
The many types of products and services offered to consumers result in consumers being more selective in terms of choosing these products and services. To be able to win the competition, companies are not only focused on products or services, but are required to be marketing-oriented. The purpose of this study is to find out: 1) an overview of service quality; 2) brand trust overview; 3) customer loyalty overview; 4) the influence of service quality on customer loyalty; 5) the influence of brand trust on customer loyalty; and 6) the influence of service quality and brand trust on customer loyalty. The subject of this study is the users of the freight forwarding service of PT Pos Indonesia Purwakarta Branch Office. The research method uses descriptive verification. The data sources used are primary and secondary. From an unknown population, a research sample of 100 people was taken, nonprobability sampling, especially incidental sampling. Data collection techniques were carried out through interviews, questionnaires, observations, and literature studies. To measure the magnitude of the influence of service quality and brand trust on customer loyalty in the use of PT Pos Indonesia Purwakarta Branch Office freight forwarding services using SPSS software version 26.0. The results of the study revealed that the influence of service quality on customer loyalty was 35.05% (low), while the influence of brand trust on customer loyalty was 45.56% (moderate). The results of the determination coefficient showed that the influence of service quality and brand trust on customer loyalty was 44.5% (moderate), while the remaining 45.5% was influenced by other factors that were not studied in this study